Răspuns :
2x/3y=8/9⇒ 2x·9=8·3y⇒ 18x=24y
x=24y/18 simplificam x=4y/3 si inlocuim in
x+y=56
4y/3+y=56
(4y+3y)/3=56
7y=56·3
y=168/7
y=24
x+24=56
x=56-24
x=32
x=24y/18 simplificam x=4y/3 si inlocuim in
x+y=56
4y/3+y=56
(4y+3y)/3=56
7y=56·3
y=168/7
y=24
x+24=56
x=56-24
x=32
[tex]\frac{2a}{3b} = \frac{8}{9} =\ \textgreater \ 24b = 18a =\ \textgreater \ 8b=6a [/tex]
Si avem apoi
[tex]a+b=56/*6[/tex]
[tex]8b+6b=336 =\ \textgreater \ b=24 =\ \textgreater \ a=56-24 =\ \textgreater \ a=32[/tex]
Si avem apoi
[tex]a+b=56/*6[/tex]
[tex]8b+6b=336 =\ \textgreater \ b=24 =\ \textgreater \ a=56-24 =\ \textgreater \ a=32[/tex]